Erosion Risk Assessment through soil erodibility, rainfall erosivity and catchment characteristics in submontaneous tract of Northwest India - M.S. Hadda,; Sanjay Arora,; D.D. Bhardwaj, (Journal of Soil and Water Conservation, 2022)
An erosion risk assessment survey of a catchment is useful in identifying those areas where, the maximum sustained productivity from a given land use is threatened by excessive soil loss. However, soil loss could be prevented by formulating appropriate conservation strategies based on the knowledge of erosion risk of the area. Keeping these points in mind, an assessment of erosion risk was made of a catchment located at Zonal Research station for Kandi Area in district Nawanshahr, Punjab, India. The mean annual rainfall aggressiveness for the area was 224.7 mm and rainfall erosivity was 567.7 m tons ha-1 cm h-1. An erosion survey of an area showed that 35.3% of the total area suffered from high to severe risk of erosion, 28.5% moderate and 36.2 % from slight to low risk of erosion. All the eastern and some western part of the area is under high and severe erosion risk. The slight to medium risk of erosion prevailed in the central and western parts of the area. This area had gentle slopes and comparatively less erodible soils because it is under substantial plant cover whereas in the remaining area, high erodibility of soils and inadequate plant cover are mainly responsible for high risk of erosion.Nomographic soil erodibility factor ‘K’ varied from0.27 to 0.42 and increases with an increase in depth of pedons in the area. The slope area relationships indicated that the North-Eastern part of the area showed greater undulation and steepness of slopes, whereas the south-western parts of the area had gentle and regular slopes. The dominant factors identified for the high to severe erosion risk are the presence of steep slopes, formation of splash pedestals, numerous deep gullies and absence of protective plant cover.